The application of politeness principles in speech acts in the 2024 presidential Election debate - Mulyono; Kisyani Laksono; Rusdhianti Wuryaningrum; Anggoro Abiyyu Ristio Cahyo (Cogent Arts & Humanities)
Language politeness is a pragmatic topic that can help identify potential presidential candidates in positioning themselves in debates. This study analyzes the application of the principle of linguistic politeness in improving the delivery of speech acts in the debate of the presidential candidates of the Republic of Indonesia in 2024. With a pragmatic approach, the analysis was conducted based on politeness strategies, politeness maxims and linguistic expressions of politeness using data from verbatim debate transcripts. The results showed that Anies Baswedan dominated the Politeness Strategy, particularly through positive politeness to build solidarity and create inclusive communication. Prabowo Subianto dominates in applying the maxim of politeness, especially the maxim of generosity to emphasize commitment to joint solutions. In addition, Prabowo Subianto also dominated the use of Politeness Linguistic Expressions, such as committers and hesitators. This research confirms that the strategic application of language politeness principles can increase the deliverability of speech acts, strengthen the candidate’s image and persuasively influence public opinion in political debates.